Himawari sea surface temperature data reveal regular internal wave activity producing cooling in the northern South China Sea - Dang, Xiaoyan; Sui, Yi; Tang, Danling; Wang, Jiujuan; Chen, Shengli (Frontiers in Marine Science, 2025)
Internal wave (IW) events occur rapidly and have a short duration, but they have a great impact on nearshore ecosystems. To address the problems of short observation time, limited range based on measured data, and low accuracy based on mesoscale satellite data for the study of IW-induced sea surface temperature (SST) change, this paper introduce high-frequency geostationary orbit satellite data combined with SST data of different times and analyze and discuss the changes and mechanisms of immediate and long-term spatio-temporal SST distributions in the northern South China Sea (SCS) caused by IWs. The results show that high-precision satellite data can reflect SST changes caused by IWs in the northeastern SCS, these being particularly significant at the Dongsha Atoll (DA) and along the northwestern continental slope, where SST can be reduced by 1°C–1.5°C, which is caused by the vertical transport of internal waves and the turbulent mixing effect of the broken internal waves, respectively. The discontinuity between the two cold centres is due to the short duration of the vertical transport of internal waves. Whereas turbulent mixing due to IW fragmentation on the continental shelf at shallower depths of 200 m, the duration of the constantly fragmented wave packets is sufficient to maintain low temperatures on the continental shelf, although the turbulent mixing effect is weaker than the vertical transport. Long-term IW activity has deepened the SST depression caused by shallow topography (shallower than 300 m) in the northeastern SCS, especially at a water depth of 200 m. Fragmentation and dissipation of IWs caused SST valleys on the continental slope as shallow as 160 m. This study validates the conclusions from methods such as moorings and modeling and has important implications for the study of IW biology.